Tax as an Instrument of Social Policy - Glazebrook, Susan (Victoria University of Wellington Law Review, 2022)
This article reviews the history of tobacco taxation in Aotearoa New Zealand and the gradual transition from the use of the tobacco tax as a revenue raising tool to an instrument of social policy and the consequences of that shift. In particular, the article examines the adverse impact of the present-day iteration of the tobacco tax on Māori and other disadvantaged groups.